The impact of change in albumin assay on reference intervals, prevalence of 'hypoalbuminaemia' and albumin prescriptions. (January 2016) - Coley-Grant, Deon; Herbert, Mike; Cornes, Michael P; Barlow, Ian M; Ford, Clare; Gama, Rousseau
Background: We studied the impact on reference intervals, classification of patients with hypoalbuminaemia and albumin infusion prescriptions on changing from a bromocresol green (BCG) to a bromocresol purple (BCP) serum albumin assay. Methods: Passing-Bablok regression analysis and Bland-Altman plot were used to compare Abbott BCP and Roche BCG methods. Linear regression analysis was used to compare in-house and an external laboratory Abbott BCP serum albumin results. Reference intervals for Abbott BCP serum albumin were derived in two different laboratories using pathology data from adult patients in primary care. Prescriptions for 20% albumin infusions were compared one year before and one year after changing the albumin method. Results: Abbott BCP assay had a negative bias of approximately 6 g/L compared with Roche BCG method. There was good agreement ( y = 1.04 x − 1.03; R 2 = 0.9933) between in-house and external laboratory Abbott BCP results. Reference intervals for the serum albumin Abbott BCP assay were 31–45 g/L, different to those recommended by Pathology Harmony and the manufacturers (35–50 g/L). Following the change in method there was a large increase in the number of patients classified as hypoalbuminaemic using Pathology Harmony references intervals (32%) but not when retrospectively compared to locally derived reference intervals (16%) compared with the previous year (12%). The method change was associated with a 44.6% increase in albumin prescriptions. This equated to an annual increase in expenditure of £35, 234. Conclusions: We suggest that serum albumin reference intervals be method specific to prevent misclassification of albumin status in patients. Change in albumin methodology may have significant impact on hospital resources.